Childhood Trauma and the Burden of Prophecy in Chigozie Obioma’s The Fishermen - OYEWOLE , Oluwatosin Ayomikun; KASIM, Isioma Glory; ADEJUMO, Funmilayo Precious (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Childhood trauma has emerged as a critical subject in contemporary literary and psychological discourse, reflecting the enduring scars left by early adverse experiences. In Chigozie Obioma’s The Fishermen (2015), trauma is not merely an outcome of physical violence but is triggered by a prophecy that destabilises the Agwu brothers’ lives. The madman’s utterance functions as a psychic intrusion, dismantling familial unity and transforming youthful innocence into suspicion, paranoia, and eventual fratricide. This paper analyses the representation of childhood trauma in the novel through the lens of psychoanalytic theory, drawing on Sigmund Freud’s concepts of repression, id, ego and super-ego. The study argues that the prophecy embodies trauma’s ungraspable quality, a linguistic event whose meaning overwhelms the child’s interpretive faculties and reemerges in destructive repetitions. By foregrounding the psychic burden carried by children, the paper reveals how Obioma explores the shattering of innocence as both a personal tragedy and an allegory of Nigeria’s fractured postcolonial state. Ultimately, the paper contends that The Fishermen situates childhood trauma at the intersection of the individual and the familial, offering insight into how prophecy, fear, and violence scar not only individual lives but also the collective consciousness of a nation.